Phytobiotics Habbatus Sauda and Garlic Meal: Are still Efficacious during the Spred of Marek's Disease Outbreak - Dono, Nanung Danar (Faculty of Animal Science, Universitas Gadjah Mada Yogyakarta, Indonesia, 2015, 2015)
When kept intensively in a closed-house poultry shed, additions of habbatus sauda (Nigella sativa; HSM) or garlic bulb meal (Allium sativum; GBM) in the diets were claimed to be efficacious used as growth promoter for broielr chickens. This study critically evaluated the effectiveness of both phytobiotics during the spread of Marek's disease outbreak. A hundred male New Lohmann day old broiler chicks were divided into 5 dietary treatments. One-way ANOVA treatment structure in a Complete Randomized Design was used in this experiment. The treatment diets were: basal diets that meet dietary requirements of the breeder, without phytobiotics supplementation (control; P1); basal diets + 1.0% HSM (P2); basal diets + 1.0% GBM (P3); basal diets + 1.0% HSM + 1.0% GBM (P4); and basal diets + 0.5% HSM + 0.5% GBM (P5). Each treatment was replicated 5 times, with 4 birds in each replicate pen. Response parameters that evaluated in this study were growth performance (average daily gain, final weight, feed intake, and feed conversion ratio) and protein - energy efficiency (protein and energy intake, protein and energy efficiency ratio), based on 5 weeks rearing period. Results showed that, when the birds were raised in tropical opened-system poultry shed during the spread of Marek's disease, dietary addition of 1.0% habbatus sauda and garlic bulb meal did not give any significant positive effects on all response variables that observed on growth performance and protein-energy efficiency parameters. It might be concluded that phytobiotics supplementation is only efficacious for improving productivity of broiler chickens when the birds are reared in closed-house poultry shed that free from disease outbreak.